ANALISIS BERKAS SINAR-X PADA PERISAI RADIASI BERBASIS POLYESTER TIMBAL ASETAT DI MURNI TEGUH MEMORIAL HOSPITAL - Dabukke, Hotromasari; Aritonang, Fitler; Sijabat, Salomo (Universitas Tadulako, 2021)
This research was about the effect of polyester resin as a matrix, and lead acetate as filler in the manufacture of X-ray radiation shields in order to determine its characteristics on physical, mechanical and thermal properties at Murni Teguh Memorial Hospital. Lead acetate was varied (0, 2, 4, 6, 8, and 10) wt% with variations in sample thickness of 0.5 cm, 0.75 cm, 1.0 cm, 1.25 cm and 1.50 cm. The results showed that the physical properties (density 1.9 gr/cm 3) on the composition of 10% wt lead acetate and 85% wt polyester resin with a thickness of 1.5 cm were the best results. The higher the lead acetate composition, the higher the density value is. The light transmission value of 83% was still in accordance with the ISO standard regarding lead glass. The results of the mechanical properties test (compression test 79 kg/cm3 and hardness test 38) were the best values at the composition of 85:10:5% wt with a thickness of 1.5 cm. This shows that the composition of 85:10:5% wt is the most homogeneous composition resulting in optimum mechanical properties. The results of the DSC test showed that an endothermic temperature of 85:10:5% wt with a thickness of 1.5 cm was the best with a temperature of 3770C. From all radiation shield sample tests, the composition of 85:10:5% wt has the best physical properties and mechanical properties in accordance with ISO and SNI-16-6656-2002 standards regarding lead glass.